SOCIAL FORESTRY DEVELOPMENT STRATEGY FOR COMMUNITY FORESTS (CASE STUDY OF THE TELA SERASAN FOREST FARMERS GROUP) - Yety Hastiana; Helen Monica Landawati; Ir. Lulu Yuningsih, S.Hut, M.Si, IPU (Sylva Jurnal Ilmu-ilmu Kehutanan, 2026)
Social Forestry is a government policy aimed at granting communities legal access to manage forest areas sustainably while simultaneously improving their welfare. This study aims to formulate a development strategy for the Community Forest managed by the Tela Serasan Forest Farmer Group in Gelumbang District, Muara Enim Regency. The research employs a descriptive qualitative method utilizing source and method triangulation through observation, interviews, and documentation. Data analysis was conducted using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) framework to identify internal and external factors influencing the group's development. The results indicate that KTH Tela Serasan possesses strengths such as legal authorization for HKm management, peat ecosystem potential, high community interest, and supportive infrastructure and accessibility. Key weaknesses include weak group institutional capacity, limited funding, a lack of forest resource inventory data, and low human resource capacity. External factors reveal opportunities such as government policy support, university involvement, the implementation of agroforestry systems, and potential corporate partnerships through Corporate Social Responsibility (CSR) programs. Threats include the high risk of peatland fires, a shortage of facilitators, and suboptimal administrative and boundary demarcation processes. Based on the SWOT analysis, the recommended priority strategy is the Strength–Opportunity (SO) strategy: optimizing internal strengths to capitalize on opportunities through institutional strengthening, peat-based agroforestry development, member capacity building, multi-stakeholder partnerships, and the sustainable marketing of community forest products.